IMPROVING THE FINANCING OF SCHOOL EDUCATION BASED ON INTERNATIONAL EXPERIENCE - Sharapova Mashkhura Azadovna (American Journals, 2025)
This study explores contemporary methodologies for funding school education in Uzbekistan and globally. It presents a comparative review of general education budget allocations across several countries, focusing on the proportion of school-level expenditures within total educational spending. The article highlights the effectiveness of public financing, the contribution of private and international funds, and the imperative to boost investments in the school sector. The findings underline the need for enhanced transparency, efficiency, and fairness in resource distribution. Based on these insights, targeted recommendations are proposed to improve Uzbekistan’s school financing framework.
Keywords: School education, financing, budget allocation, Uzbekistan, GDP, efficiency, government expenditures, comparative analysis.